PENGARUH MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION TERHADAP HASIL BELAJAR DITINJAU DARI GAYA BELAJAR SISWA - Yuni Permatasary; Agus Abhi Purwoko; Muntari Muntari (Jurnal Penelitian Pendidikan IPA, 2018)
The aim of this study are: (1) to determine differences on learning achievement between  students who obtained PBI learning model and who received conventional learning models; (2) to determine the different of students achievement on different learning styles (visual, auditory and kinesthetic). The population of this study on all class X SMAN 7 Mataram students (570 students). Two classes were chosen as sample of this study (64 students). Instruments in this study consisted of paper and panel test of learning achievement and quetsionair of student’s learning styles. The results of data analysis showed: (1) PBI learning model significantly influence on student learning achievement; (2) the learning style does not significantly affect to learning achievement.Keywords: Problem Based Instruction, learning styles, student learning achievement